Prediction of Ternary Vapor-Liquid Equilibria for Alcohols + Glycerol + Water Systems to Enhance the Quality of Glycerol as Biodiesel Side Product - D. Setiawati, Eviana; Mustain, Asalil; Wibawa, Gede (Institut Teknologi Sepuluh Nopember, 2015)
Fossil fuels as the primary energy resources around the world cause significant negative effect on atmosphere. Recently, biodiesel, which primarily produced from renewable resources, has received great attention because of its environmental benefits. Higher chain of alcohols, such as butanol, may be used as solvent to produce biodiesel with glycerol as byproduct. In order to enhance the quality of glycerol as biodiesel side product which meets food and pharmaceutical standards, vapor-liquid equilibria (VLE) data for ternary systems consisting of 1-butanol, 2-methyl-1-propanol, glycerol and water are required to design and optimize the separation process of glycerol. In this work, the prediction of ternary VLE for (1-butanol / 2-methyl-1-propanol + glycerol + water) using UNIFAC model were determined at various temperatures and compositions and compared with the experimental data giving Average Absolute Deviations (AAD) less than 5.7%. The results indicated that UNIFAC was a reliable model for phase equilibria predictions in the mixtures containing of glycerol